A Simple and Sensitive HPLC/UV Method for Determination of Meloxicam in Human Plasma for Bioavailability and Bioequivalence Studies - Laila H. Emara, Maha F. Emam, Nesrin F. Taha, Hala M. Raslan, Ahmed A. El-Ashmawy (Journal of Applied Pharmaceutical Science, 2017)
An HPLC/UV method to monitor meloxicam (MX) in human plasma was developed and properly validated. This method was based on a reversed-phase chromatographic analysis using C18-Symmetry column and a mobile phase consisting of acetonitrile: deionized water [50:50 (% v/v)] adjusted to pH 3 with glacial acetic acid. The detection wavelength was 360 nm using piroxicam as an I.S. The developed HPLC method was linear, sensitive, accurate, precise, selective and stable. This method exclusively provided a LLOQ of 5 ng/mL and ULOQ of 3000 ng/ml which could be considered as an excellent and economical method for carrying-out BA/BE studies. The determination of pharmacokinetics of single oral dose (15 mg/tablet) administered to healthy human male volunteer was carried-out to compare the bioavailability of three different MX products with a washout period of 8-days between treatments. Moreover, a comparative in vitro dissolution study of the three products using USP#4 (the Flow-through cell, FTC) has been carried-out prior to the in vivo test. The pharmacokinetic data revealed that the developed HPLC method was sensitive enough to monitor the multiple-peak phenomena characterized for MX absorption. Where, the first Cmax appeared at 4.5–5.5 hrs and the second at 10–12 hrs, for the tested products.
Keywords: HPLC/UV, Meloxicam, Validation, Pharmacokinetic, Stability.